Breeding tef [Eragrostis tef (Zucc.) trotter]: conventional and molecular approaches - Assefa, K.; Yu, J.K.; Zeid, M.; Belay, G.; Tefera, H.; Sorrells, M.E. (Wiley, 2011)
Tef [Eragrostis tef (Zucc.) Trotter] is an important food staple cereal crop in Ethiopia. Despite its importance in the Ethiopian agriculture, there are constraints that need to be addressed through scientific research. The major constraints are low yield of landrace cultivars under widespread cultivation, susceptibility to lodging and a lack of knowledge concerning the genetic control of agronomic traits. Conventional tef breeding efforts started in the late 1950s, and since then a total of 24 varieties have been developed and released. Yield gain from tef breeding has been linear with an average annual increase of 0.8%. Tef genomics has provided much molecular genetic information on important agronomic traits. More than 1500 PCR-based molecular markers have been developed and several genetic linkage maps based on intra- and inter-specific crosses have been constructed. Results from quantitative trait loci studies have provided information necessary for marker-assisted selection. Lodging is the number one cause of yield loss in tef. Recently, molecular breeding techniques and biotechnologies are being employed to understand the genetic control of lodging.